Healthcare Professionals’ Experiences with Vocational Rehabilitation for People with Inflammatory Arthritis - Madsen, Anne Birgitte; Primdahl, Jette; Christensen, Jeanette Reffstrup; Bremander, Ann; Madsen, Christina Merete Tvede (Journal of Occupational Rehabilitation, 2025)
Purpose: To explore healthcare professionals' (HPs’) experiences of work-related challenges among people with inflammatory arthritis (IA). Methods: A qualitative, interview study using a hermeneutic approach was planned. HPs with different professional backgrounds working with people with rheumatic diseases were recruited. An interview guide was developed according to relevant literature. The analysis followed Graneheim and Lundman’s qualitative content analysis. Results: Twenty-one HPs representing two municipalities, three hospitals, a university college and one patient organisation participated in individual semi-structured interviews. The analysis derived three themes: (1) Work identity and living with IA. The disease causes emotional and economic effects regarding fulfilling roles in everyday life, including work; (2) Opportunities and challenges when supporting patients. Promoting and inhibiting factors that affect retention in the labour market include organisational factors at work, opportunities for involving the patient’s relatives and working interprofessionally and cross-sectorally; and (3) Cooperation with employers. People with IA use different strategies and opportunities for compensatory schemes to maintain work. Cooperation with employers is an important part of vocational rehabilitation. Conclusion: HPs experience that people with IA find it difficult to manage their everyday life, including work. HPs want to support people with IA to maintain their jobs but find it difficult if the patient has not informed the employer about the disease. This study clarifies the need for vocational rehabilitation to support people with IA to stay in work, from time of diagnosis through hospitalisation, municipal rehabilitation and job clarification.
Keywords: Axial spondyloarthritis; Complex intervention; Psoriatic arthritis; Rheumatoid arthritis; Work rehabilitation; WORK-ON